Effect of insecticide impregnated ear tags on horn fly populations and suckling calf performance - Simms, D.; Willman, T.; Schalles, R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three trials were conducted to determine the effect of insecticide impregnated ear tags on horn fly counts and weight gain of suckling calves. In trials 1 and 2, cow calf pairs on two Kansas ranches were assigned to these treatments: 1) Control - no tag, 2) Cows Only - 1 tag per cow, 3) Calf Only - 1 tag per calf, and 4) Cow and Calf - 1 tag each. Each tag treatment was in a separate pasture. All insecticide tag treatments reduced (P<.05) horn flies on cows and calves in July and August; however, by September the tags were only reducing (P<.05) flies on cows. While the weight gain response to tags was variable, when trials were combined, all tag treatments increased (P<.05) calf gains over controls. Using a single tag per cow was better (P<.05) than a single tag per calf, while tagging both the cow and calf was no better than either single tag treatment. Average fly counts for each pasture were negatively correlated with calf weight gains indicating a strong relationship between fly populations and calf performance. In trial 3, apparent horn fly resistance to the insecticide in the tags resulted in terminating the trial mid-summer. Research in Kansas and other states indicates that horn fly resistance to pyrethroid insecticides is becoming a common problem which means that producers may need to revert to previously used methods of horn fly control.
Keywords: Beef; Ear tags; Insecticide; Performance